2010
DOI: 10.1017/s031716710001012x
|View full text |Cite
|
Sign up to set email alerts
|

Conversion Disorder after Surgery in a Brain Tumour Patient

Abstract: We describe a case of conversion disorder in a young lady who had just been operated on for a glioma. CASE REPORTA 31-year-old lady presented two years ago with seizures manifesting as jerking of her right arm and leg. Neurological examination revealed no focal deficits. Brain imaging revealed the presence of a small lesion in her left mesial posterior frontal lobe, just anterior to the motor strip ( Figure 1). The appearance was compatible with a low grade glioma. There was no perilesional edema, enhancement,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The risk factors for this disease include female sex, lower educational level, physical or sexual abuse, emotional trauma, pre-existing psychopathology, and a history of serious medical illness 2) . Furthermore, Khu et al noted that the etiology for conversion disorder was unclear, but suggested that it was caused by severe stress, emotional conflict, or an associated psychiatric disorder 5) . Nakagawa et al speculated that conversion disorder developed due to lack of communication and excessive stress 8) .…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for this disease include female sex, lower educational level, physical or sexual abuse, emotional trauma, pre-existing psychopathology, and a history of serious medical illness 2) . Furthermore, Khu et al noted that the etiology for conversion disorder was unclear, but suggested that it was caused by severe stress, emotional conflict, or an associated psychiatric disorder 5) . Nakagawa et al speculated that conversion disorder developed due to lack of communication and excessive stress 8) .…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection of WHO I gliomas such as pilocytic astrocytoma, is clearly beneficial, however the value of removal of more infiltrative gliomas is not so clear and remains the subject of controversy 5,6 . Early resection may cause neurological impairment [5][6][7] , when symptoms can often be controlled with medications until tumor progression is documented. Physicians' and surgeons' opinions on management range from early surgical resection to observation until surgery (and adjuvant treatment) becomes necessary.…”
Section: Physicians Can Help Ease Such Irrational Deductions Bymentioning
confidence: 99%